Thermoelectric nanocrystals for energy conversion applications - Chang, Lu. (2011)
The project studied the thermoelectric nanocrystals for energy conversion applications. We investigate the thermopower of few layers graphene (FLG) films and the result proves that the property could be greatly enhanced up to ∼700 μV/K after oxygen plasma treatment. The electrical conductivities of the oxygen plasma treated FLG films remain high, for example, ∼104 S/m, which results in power factors as high as ∼4.5×10-3 WK-2 m-1. In comparison, the pristine FLG films provides a maximum thermopower of ∼80 μV/K with an electrical conductivity of ∼5×104 S/m. The proposed mechanism is due to generation of local disordered carbon that opens the band gap.